ASSESSMENT OF ANTIMICROBIAL ACTIVITY OF BIO-OIL FROM PONGAMIA GLABRA, MESUA FERREA AND PARACHLORELLA SPP DEOILED CAKE - MAYUR. M. PHUKAN; RAHUL S. CHUTIA; RAHUL KUMAR; D. KALITA; B. K. KONWAR; R. KATAKI (International Journal of Pharma and Bio Sciences, 2013)
The present study deals with the assessment of antimicrobial activity (antibacterial, antifungal and antiyeast) of bio-oil from Pongamia glabra, Mesua ferrea and Parachlorella spp deoiled cake. The bio-oil from the respective deoiled cakes were obtained via the process of pyrolysis (ambient to 500°C at a heating rate of 40°C/min) in a vertical tubular fixed bed reactor in nitrogen atmosphere. Bio-oil from Mesua ferrea deoiled cake (BMFDC) and Pongamia glabra deoiled cake (BPGDC) recorded the most effective Zone of Inhibition (ZOI) against S. aureus viz., 28 and 29 mm respectively. BMFDC and BPGDC were more effective in terms of antimicrobial efficacy in contrast to bio-oil from Parachlorella deoiled cake (BPCDC). The antimicrobial activity of the bio-oil samples may be due to the presence of phenolic and carboxyl groups (detectable by FTIR spectroscopy). The results of this study indicate the presence of bio-active agents in bio-oils which may lead to development of new pharmaceuticals.